Thermally stable metal–organic framework based iron 2,6-naphthalenedicarboxylic catalyst (Fe-NDC) for syngas conversion to olefin - Ahmed E. Rashed; Mohamed S. Nofal; Ahmed Abd El-Moneim (Scientific Reports)
Abstract Olefins are the backbone of the petrochemical conversion industries, like polymers, plastic, lubricating oil, surfactants, and synthetic fuels. It is a wide but challenging process to customize. Metal–organic frameworks (MOFs) are highly regarded for their potential in Fischer–Tropsch synthesis (FTS), yet they often have inadequate thermal stability. This study demonstrated the remarkable potential of the Fe-NDC MOF. It maintains its initial structure until it reaches a temperature of 500 °C (Fe@C-500), which is efficient for syngas conversion to olefin. The Fe@C-500 catalyst exceeded a twofold increase in the ratio of olefin to paraffin compared to Fe@C-600 (2 vs. 0.8). The maintained structure of Fe@C-500 enhances the transport of reactants and restricts the hydrogenation of olefins. The Fe@C-500 catalyst showed ~ 50% and 27% selectivity to total olefin and light olefin, respectively, with a Fe-time yield (FTY) for light olefins of 180 mmolCO g−1 Fe h−1. In contrast, Fe@C-600 exhibits a shift in product selectivity towards paraffin (~ 70%) at a lower FTY for light olefins of 130 mmolCO g−1 Fe h−1. The performance of the Fe@C-500 catalyst is particularly intriguing and warrants further investigation. Retaining the porous structure of MOF-derived catalysts might greatly enhance olefin production.